THE ROLE OF SQ3R STRATEGY ON MATHEMATICAL COMMUNICATION ABILITY AND SELF REGULATED LEARNING OF SEVENTH GRADE STUDENT - Barnas Barnas; Utari Sumarmo; Mumun Syaban ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The study was a pre-test -post test experimental control group design having a goal to examine the role of SQ3R strategy and mathematics prior ability (MPA) on students’ mathematical communication ability  (MCA) and self regulated learning (SRL). The study involved 68 seventh grade students, a mathematical communication test, a mathematical  SRL scale, and a perception on SQ3R strategy scale. The study found that on MCA, its Gain, and on SRL students getting treatment by SQ3R strategy attained better grades than the grades of students taught by conventional teaching, but the grades of MCA were still at low level, and of SRL the grades were at medium level. The other findings, there was high association between MCA and SRL, and students performed high perception toward SQ3R strategy.